Novice Teacher Recruitment and Retention in a Midwestern State: An Exploration of Contextual Factors - Nicole D. Schutter; Erin Lehmann (Theory & Practice in Rural Education, 2024)
Teacher recruitment and retention consistently emerged as problematic in research and practice. This was particularly true in difficult-to-staff areas, such as rural school districts in the United States. As the teacher pipeline continued to decrease and various challenges plagued the field, this problem quickly became a crisis. The present study aimed to lift novice teachers' voices in rural and remote rural areas of a Midwestern State better to understand individuals' experiences in a rural setting and contribute to the current knowledge base of rural teacher recruitment and retention. Eleven participants in this qualitative phenomenological study aimed to uncover the specific contextual factors that influenced their experiences as novice teachers in a rural Midwestern State. Interviews revealed the need for direct support from administrators and colleagues to create a sense of belonging, which was imperative to positive novice teacher experiences. The need for appropriate preparedness within their preservice experiences and coursework, as well as solid induction and mentoring programs once hired, surfaced during the interviews. Rural-specific field experiences paired with comprehensive induction and mentoring programs focused on specific feedback prepare preservice teachers and novice teachers for successful rural teaching and living. Intentional recruitment efforts, including grow-your-own programs for future teachers and partnerships between rural school districts and teacher preparation programs, boosted the pipeline of novice teachers for rural areas.